Effect of Personality, Individual Characteristics, and Safety Management on Safety Performance at PT PAL Indonesia - Aderilla, Savira; Widajati , Noeroel; Guan , Ng Yee; Dwiyanti, Endang (Universitas Airlangga, 2024)
Introduction: PT PAL Indonesia is one of the largest shipyard industries in Indonesia, Based on the results of the survey conducted, there were several unsafe acts and unsafe conditions observed. The aims of this study aim to analyze the effect of personality, characteristics of individuals and safety management practices on safety performance of workers in the Commercial Ship Division of PT PAL Indonesia Surabaya. Method: This study used a cross-sectional design and simple random sampling method, involving 104 worker samples from a population of 139 workers. The dependent variable was personal safety performance, while the independent variables were personal awareness, safety management practices safety training and individual characteristics. Primary data were collected through questionnaires, observations and interviews. This study includes univariate analysis, bivariate analysis with Chi-square test and multivariate analysis using logistic regression analysis. Results: Based on the results of logistic regression analysis, the effect of conscientiousness personality with safety performance (ρ=0.013), the effect of safety management practices with safety training (ρ=0.000), the effect of age variables with safety performance (ρ=0.024) and the effect of working period variables with safety performance (ρ=0.024). Conclusion: There are effects of conscientiousness, personality, age, working period, safety management practices, and safety training on safety performance of workers at PT PAL Indonesia in 2023. This research can improve work safety performance by understanding the factors that influence it and companies can design more effective safety strategies.